Determinants of loyalty in destination branding: perspective from supply side - Emmanuel Chao (Cogent Business & Management, 2024)
The Tourism sector has become increasingly competitive globally, and destination branding has emerged as one of the strategic tools for establishing a competitive edge. This study attempted to discover the determinants of loyalty in destination branding from the supply side perspective. This study was conducted in the Tanzania mainland using a cross-sectional survey research design and data were collected data from 302 respondents. The results were analyzed using Structural Equation Modelling. The findings unveiled that local residents' engagement has a positive influence on loyalty towards destination branding when mediated with destination identification. The findings have also shown that when local residents develop strong identification towards the destination, they tend to express commitment to destination branding.
Keywords: 650; Local residents' engagement; loyalty in destination branding; destination brand identity; destination identification